Model Rapid Application Development Dalam Pengembangan Sistem Reservasi dan Penyewaan Kamar Hotel - Sofiansyah Fadli (Jurnal Informatika dan Rekayasa Elektronik, 2018)
The development of computerized technology at this time greatly increased, almost in all business or business field utilizing computer technology as a medium of information to obtain information fast and accurate. The Queen Hotel is one of many existing hotels and has stood for the moment and has not utilized computer technology, especially in terms of reservation and hotel room rental to manage data and information for guests or visitors using services at the Queen Hotel. One of the development of SDLC is Rapid Application Development (RAD) model which can also be used in system development by giving priority to time. In this study, the system designed and built applying the Rapid Application Development (RAD) model in which the design stage and workmanship of the system is relatively short around 60-90 days. This system is an effective media in the management of data reservasi (The data of the person who has reserved the room) and hotel room rental, facilitate officers in managing data in accordance with the part and position, facilitate the management of transaction data, reduce the level of unwanted errors and simplify the maintenance of data related to reservation transactions and hotel room rental.